The influence of the CTIP Polymorphism, Q418P, on Homologous Recombination and Predisposition to Radiation-Induced Tumorigenesis (mainly rAML) in Mice - Patel, A; Anderson, J; Kraft, D; Finnon, R; Scudamore, C; Manning, G; Bulman, R; Brown, N; Bouffler, S; O'Neill, P; Badie, C (Radiation Research Society, 2016)
Exposure to ionizing radiation increases the incidence of acute myeloid leukemia (AML), which has been diagnosed in Japanese atomic bombing survivors, as well as patients treated with radiotherapy. The genetic basis for susceptibility to radiation-induced AML is not well characterized. We previously identified a candidate murine gene for susceptibility to radiation-induced AML (rAML): C-terminal binding protein (CTBP)-interacting protein (CTIP)/retinoblastoma binding protein 8 (RBBP8). This gene is essential for embryonic development, double-strand break (DSB) resection in homologous recombination (HR) and tumor suppression. In the 129S2/SvHsd mouse strain, a nonsynonymous single nucleotide polymorphism (nsSNP) in Ctip, Q418P, has been identified. We investigated the role of Q418P in radiation-induced carcinogenesis and its effect on CTIP function in HR. After whole-body exposure to 3 Gy of X rays, 11 out of 113 (9.7%) 129S2/SvHsd mice developed rAML. Furthermore, 129S2/SvHsd mouse embryonic fibroblasts (MEFs) showed lower levels of recruitment of HR factors, Rad51 and replication protein A (RPA) to radiation-induced foci, compared to CBA/H and C57BL/6 MEFs, isolated from rAML-sensitive and resistant strains, respectively. Mitomycin C and alpha particles induced lower levels of sister chromatid exchanges in 129S2/SvHsd cells compared to CBA/H and C57BL/6. Our data demonstrate that Q418P nsSNP influences the efficiency of CTIP function in HR repair of DNA DSBs in vitro and in vivo, and appears to affect susceptibility to rAML.